ANALYSIS OF MATHEMATICAL LITERACY AND CREATIVITY: IMPLEMENTATION OF HABITS OF MIND AND SELF ESTEEM STRATEGIES IN STUDENTS - Maharani Fitriana; Achi Rinaldi; Siti Ulfa Nabila (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The purpose of this study is to determine the influence of MHM learning strategies on mathematical literacy and mathematical creative thinking reviewed from the self-esteem of students at SMP Negeri 5 Bandar Lampung in grade VIII. This study uses the analysis of the two-way manova test with the level of. In the results of the manova test, the score for the mathematical literacy test was obtained so that it was rejected, it can be interpreted that there is a significant influence between MHM and conventional learning strategies, in the creative thinking test it has a value so it is rejected, which means that there is a significant influence between MHM and conventional learning strategies. In self-esteem and literacy, there is a significant influence because of value, namely, while self-esteem with creative thinking has a value which is rejected can be interpreted as a significant influence. When viewed simultaneously, there is a significant influence between the mathematical literacy test and mathematical creative thinking with the value and which of the value  is rejected.